OPTIMALISASI PEMBIAYAAN MURABAHAH BERPRINSIP BAGI HASIL PADA BANK SYARIAH DI INDONESIA 2010 - 2015 - Windasari Rachmawati; Abdul Karim; Abdul Manan (Universitas Semarang, 2017)
This study research aim to identify whether the factors of DPK, NPF, Inflation and CAR have an effect on murabaha financing. The research method using multiple regression statistic test.One of the products of Islamic banks that are currently booming is Murabahah financing. Murabahah financing is the sale and purchase of goods at the price of origin with additional profits yanng agreed. The technical term of syari'ah murabahah banking is defined as an agreement agreed between Bank Syariah with customers, where the Bank provides financing for the purchase of raw materials or other working capital required by the customer, which will be repaid by the customer at the selling price of the bank (the purchase price of the profit margin bank) at the stipulated time. This study was conducted to examine the effect of DPK, NPF, INFLATION and CAR variables on murabahah financing in sharia banks registered in Indonesian banks during the period 2010-2015. The criteria for selecting samples using purposive sampling. The sample of research is 12 sharia banking companies.Based on the results of the analysis and discussion conducted it can be concluded that the independent variables in this study measured using the committee DPK, Inflation, NPF does not affect murabahah financing, this is because the murabahah financing is not well known public, when compared to mudharabah financing and mutlaqah financing . This can be seen on average during the years 2010 - 2015. DPK with a significance level of 0.522> 0.005, inflation 0.415> 0.005, and NPF 0.512> 0.005.Capital asset ratio affects murabahah financing with a value of 0.001 <0.005